2001
DOI: 10.1063/1.1332795
|View full text |Cite
|
Sign up to set email alerts
|

Crystal field, phonon coupling and emission shift of Mn2+ in ZnS:Mn nanoparticles

Abstract: The Mn2+ emission wavelengths are at 591, 588, 581 and 570 nm, respectively, for the ∼10, ∼4.5, ∼3.5 nm sized nanoparticles and the ZnS:Mn nanoparticles formed in an ultrastable zeolite-Y. To reveal the cause for the shift, the crystal field and phonon coupling were investigated. The results show that the predominant factor for the shift is the phonon coupling, whose strength is size dependent and is determined by both the size confinement and the surface modification of the nanoparticles. Although the crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
162
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(177 citation statements)
references
References 43 publications
14
162
0
1
Order By: Relevance
“…The relation E Stokes = (2S À 1) ho is used in many reports, 1,[12][13][14][15][16][17][18][19] while other works use the alternative relation E Stokes = 2S ho (ref. [20][21][22][23][24], or are ambiguous about it. 25 New insights in the relation between the experimentally observed Stokes shift and the Huang-Rhys parameter, with the aim to resolve this ambiguity, can be realized using simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The relation E Stokes = (2S À 1) ho is used in many reports, 1,[12][13][14][15][16][17][18][19] while other works use the alternative relation E Stokes = 2S ho (ref. [20][21][22][23][24], or are ambiguous about it. 25 New insights in the relation between the experimentally observed Stokes shift and the Huang-Rhys parameter, with the aim to resolve this ambiguity, can be realized using simulations.…”
Section: Introductionmentioning
confidence: 99%
“…O uso do ZnO como material fotocatalisador para a degradação de poluentes ambientais tem sido vantajoso em relação a outros materiais devido à sua natureza não-tóxica, seu baixo custo e alta reatividade, 17,18 como também ocorre para o dióxido de titânio. O óxido de zinco tem sido sintetizado por vários métodos, tais como sol-gel, 19,20 de estado sólido, 21,22 de condensação da fase gasosa 23 e método químico de precipitação em fase líquida. 24,25 O estudo do efeito de vários fotocatalisadores na descolorização e degradação do azo corante Reactive Yellow (RY14) em solução aquosa revelou a seguinte ordem de reatividade: ZnO > TiO 2 -P25 > TiO 2 (anatase).…”
Section: Introductionunclassified
“…The PLE and PL spectra of ZnS:Mn/PVP nanoparticles excited by different excitation wavelengths showed that in these nanoparticles there exhibited two excitation mechanisms: the indirect excitation through ZnS host and the direct excitation of 3d-electrons of Mn 2+ cations [15]. The excitation by 344 nm radiation with photon energy near the band gap energy of ZnS is mainly the indirect excitation.…”
Section: Iii3 the Influence Of Pvp On Absorption And Radiation Tranmentioning
confidence: 99%
“…6(a)). These bands could be assigned to the absorption transitions of 3d 5 electrons from 6 A 1 ( 6 S) ground state to 4 E( 4 D), 4 T 2 ( 4 D), 4 A 1 ( 4 G)-4 E( 4 G) and 4 T 2 ( 4 G) excited states of Mn 2+ cations in ZnS host lattice, respectively [15]. For PVP-capped ZnS:Mn nanoparticles with mass from 0.3 to 0.8 g, the intensity of these bands increased and achieved the maximum at mass equal 0.7 g (see Fig.…”
Section: Iii3 the Influence Of Pvp On Absorption And Radiation Tranmentioning
confidence: 99%